Variability in soil carbon and nitrogen storage across a chronosequence of Pinus kesiya plantations in the Central Highland, Vietnam - Cuong, L. V.; Quy, N. V.; Karam, D. S.; Hung, B. M.; Chau, M. H.; Long, L. N.; Manh, V.; Tuan, N. T.; Quy, N. V.; Ngoan, T. T. (Corvinus University of Budapest, 2025)
Plantations play a crucial role in the global nutrient cycle by accumulating soil carbon (C) and nitrogen (N). However, the relationship between stand features, soil physicochemical properties, and soil C and N storage in plantations of various ages has not been clearly understood. This study aims to clarify these complex relationships by investigating soil C and N stocks at three soil depths (0−20, 20−40, and 40−60 cm) across a chronosequence of Pinus kesiya Royale ex. Gordon plantations aged 5, 11, 15, 25, and 35 years in the Central Highland region of Vietnam. The results demonstrated that the contents of soil organic carbon (Sc) and total soil nitrogen (Sn), as well as the soil C:N ratio, all increased during forest development. The contents of Sc and Sn, along with the soil C:N ratio, significantly decreased as soil depth increased throughout forest development. Stocks of total Sc (SSc) and total Sn (SSn) also increased during forest development, rising from 101.20 Mg ha⁻¹ to 226.83 Mg ha⁻¹ and from 5.43 Mg ha⁻¹ to 8.76 Mg ha⁻¹, respectively. SSc and SSn appear to respond to afforestation by predominantly aggregating just beneath the ground surface. SSc and SSn decreased with increasing soil depth. SSc demonstrated a significant positive association with SSn. The results from the structural equation model (SEM) analysis indicated that SSc and SSn were significantly influenced by soil variables such as bulk density, pH, and clay content, as well as forest stand traits like plant biomass. In general, SSc and SSn were more significantly affected by soil traits than by stand traits. Our findings contribute substantially to the scientific knowledge necessary for developing sustainable management strategies and techniques for P. kesiya forests to enhance their productivity.